Pengaruh Suku Bunga, Inflasi, Nilai Tukar Rupiah, dan BOPO terhadap Kinerja Perbankan Syariah di Bank BRI Syariah Periode 2015-2020 - Nur Rosi Awaliatun Nikma; Mahmudatus Sa'diyah (Jurnal Rekoginisi Ekonomi Islam, 2022)
This study aims to determine the effect of interest rates, inflation, rupiah exchange rates, and BOPO (operational costs and operating income) on the performance of Islamic banking at BRI Syariah Bank for the 2015-2020 period. This type of research used is quantitative. The data collection method uses secondary data in the form of quarterly financial statement ratios of BRI Syariah Bank for the 2015-2020 period. The analytical method used in this research is multiple linear regression method. The results of the study indicate that the variables of interest rates, inflation, rupiah exchange rates, and BOPO simultaneously affect the performance of Islamic banking at Bank BRI Syariah for the 2015-2020 period. Partially, interest rates and the rupiah exchange rate have no effect on ROA (return on assets), while inflation and BOPO have a significant effect on ROA (return on assets).